Implementasi Connection Sharing Internet Menggunakan Mikrotik Pada Siswa SMK XYZ Palembang - Mahmud; Yarza Aprizal (AMMA : Jurnal Pengabdian Masyarakat, 2023)
The connecting media between one device and another is the Internet, in this era the internet cannot be separated anymore in the student learning process, including students of SMK XYZ Palembang. XYZ Palembang Vocational School is one of the Vocational Schools in Palembang. Computer and Network Engineering which is one of the majors at SMK XYZ Palembang which has adequate laboratory facilities which of course can be used to make case studies of computer networks that are suitable for use in the world of work and industry. The use of network laboratories is currently only intended for educational purposes based on a predetermined curriculum. Having the ability or concentration makes added value for someone in getting a job. One of the skills needed is the configuration of a computer network. The need for knowledge of proxy configurations to be ready to enter the world of work, so held training on Implementation of Internet Connection Sharing Using Mikrotik for SMK XYZ Palembang students. The result is 79.17% of service participants have understood the material that has been presented, which means that this activity has gone well.